THREE CASES WITH BURKITT LYMPHOMA PRESENTING WITH CHOLESTASIS - Fatma Tuba YILDIRIM (Elsevier, 2021)
Case report: Cholestasis secondary to neoplasm is rare in children. It is also rare in Burkitt lymphoma and may be cause to treatment delay. We report 3 cases diagnosed with Burkitt lymphoma with cholestasis. All patients had jaundice and high direct biluribin levels. They were given LMB chemotherapy protocol. After COP chemotherapy, cholestasis disapperead rapidly in all patients. In conclusion, cholestasis at initial resolves rapidly with chemotherapy despite high liver function tests in Burkitt lymphoma.